2023
DOI: 10.1186/s12967-023-04077-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic alterations of cerebrospinal fluid cell-free DNA in leptomeningeal metastases of gastric cancer

Abstract: Background Leptomeningeal metastases (LM) were rare in gastric cancer (GC), and GC patients with LM (GCLM) generally suffer from poor prognosis. Nevertheless, the clinical utility of cerebrospinal fluid (CSF) circulating tumor DNA (ctDNA) was underinvestigated in GCLM. Methods We retrospectively studied 15 GCLM patients, and all patients had paired primary tumor tissue samples and post-LM CSF samples while 5 patients also had post-LM plasma samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…What's more, we demonstrated that CSF ctDNA has a signifcantly higher detection rate than plasma. This result is consistent with previous study which show that CSF ctDNA exhibite a more comprehensive genetic landscape than plasma of CNS metastases [14,16,17,19]. Previous studies have compared the detection rate of EGFR and found that it is higher in CSF than plasma.…”
Section: Discussionsupporting
confidence: 93%
“…What's more, we demonstrated that CSF ctDNA has a signifcantly higher detection rate than plasma. This result is consistent with previous study which show that CSF ctDNA exhibite a more comprehensive genetic landscape than plasma of CNS metastases [14,16,17,19]. Previous studies have compared the detection rate of EGFR and found that it is higher in CSF than plasma.…”
Section: Discussionsupporting
confidence: 93%
“…Few rare GC cases metastasize in the leptomeningeal region, giving rise to gastric cancer with a leptomeningeal metastasis (GCLM) subtype. Quantifying post-therapy cfDNA in the CSF of such cases provides various prognostic clues, such as this study ( Chen et al, 2023 ), which reported that reduced cfDNA levels in the CSF indicated better PFS in GCLM patients. In such cases, identifying levels and genomic alterations in CSF ctDNA could hold promising potential to provide prognostic decisions and clinical assessment.…”
Section: Circulating Tumor Dnamentioning
confidence: 90%